Pembangkit Energi Listrik Hybrid Mini Menggunakan Tenaga Surya Sebagai Sumber Energi Alternatif - Arbi Nugraha; Pola Risma; RD Kusumanto (Journal of Applied Smart Electrical Network and Systems, 2021)
Hybrid system is the concept of combining two or more different energy sources to meet the needs of existing electricity loads. The advantage of this solar energy is that it is non-polluting, inexhaustible and can be used directly or indirectly and is energy for all time. In this study, a tool designed for hybrid electric energy generation using solar energy and wind energy. The solar panel used is 50 Wp Polycrystalline type and The wind generator used is MY-1016 with an output power of 350 Watt. In this study, a system for monitoring the power generated electric energy generator using solar energy is needed which consists of components such as current sensors INA219, Arduino Mega 2560 and displayed in real time using the Internet of Things (IOT).